Sistem Informasi POS (Point Of Sale) untuk Penjualan berbasis Web pada Toko Anggrek Javina - Reinaldi Guista Pradana Ismail; Bayu Rahayudi; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
PT. JAVINA is a company engaged in the breeding, cultivation and trading of orchids and other agricultural products. In handling transactions, the company still uses conventional methods, namely written notes. This is of course less efficient and non-digitized transaction data slows down the cashier's income reporting process. In addition, the company is developing an e-commerce named isitaman.com. When e-commerce stuffing is running later, stock synchronization between products in the checkout (online sales) and at the cashier (offline sales) will certainly be a problem for the company. Therefore by utilizing a POS information system is expected to increase the efficiency of the company's business processes. As well as the transaction data management process becomes more structured and efficient. Then with a web-based information system that will facilitate integration in terms of synchronizing product stock data with e-commerce companies that are currently being built. The Javina POS information system will be built using a framework called Laravel with the PHP programming language and utilizing MySQL as database management.